Potentially Traumatic Events, Posttraumatic Stress Disorder, and Depression among Adults in Puerto Rico - Overstreet, Cassie; Berenz, Erin C.; Sheerin, Christina; Amstadter, Ananda B.; Canino, Glorisa; Silberg, Judy (Frontiers in Psychology, 2016)
The aims of the current study were to examine the prevalence of potentially traumatic events (PTEs), posttraumatic stress disorder (PTSD; data available in males only), and depressive symptoms in a Puerto Rican sample of 678 adult caretakers (50% female) of twins participating in the Puerto Rican Infant Twin Study. The World Health Organization Composite International Diagnostic Interview version 3.0 (CIDI 3.0) was utilized to assess rates of PTEs, PTSD, and depression among male participants while an abbreviated version of the CIDI 3.0 and the Mood and Feelings Questionnaire were administered to females to assess PTEs and depressive symptoms. Significantly more males than females reported exposure to a PTE (76.6% vs. 44.2%, 2=64.44, p<.001). In males, endorsement of multiple PTEs was associated with increased level of PTSD symptomatology ( = .33, p < .001). With regard to depression, a similar dose-response relationship was found in both males and females, with depressive symptoms increasing as number of PTEs increased (s = .15, .16, ps < .05). Exposure to an attack with a weapon was significantly associated with increased depression symptoms in both males and females (s=.24, .20, ps<.01, respectively). These findings highlight the need for identification of putative risk and resilience factors among PTE-exposed individuals in Puerto Rico.